"New Regionalism" and Its Implementation in Ukrainian Legislation: The Terminology and the Political Implications - Melnyk, Nazarii (Verbum, 2023)
This paper investigates the terminology associated with "New regionalism" and its integration into Ukrainian legislation, analyzing its political and administrative implications. "New regionalism" is a contemporary administrative-territorial reform, with a focus on the principle of subsidiarity, which minimizes central authority intervention in local affairs. While not explicitly present in its regulations, certain subsidiarity elements are part of Ukrainian law. The study explores the adoption and implementation of "New regionalism" principles and terminology within the country's legal discourse. The second aim of the study was to examine how "New regionalism" could potentially influence the political dynamics and administrative structures, particularly in the context of decentralization efforts. By employing systematic and comparative methodologies alongside principles of dialectical analysis, the study offers insights into the evolving landscape of Ukrainian political and administrative terminology alongside its structures, which might play a crucial role in the context of the Russian-Ukrainian conflict.
Keywords: New regionalism; terminology; political discourse; subsidiarity; regional political subjects; Ukraine; regionalization